Between Czechs and Hungarians: Constructing the Slovak National Identity from 19th Century to the Present - Hudek, Adam (History compass, 2011)
Over the entire existence of the Slovak historical science, the formation of Slovak ‘national consciousness’ has been always considered a research topic of great importance. It is a quite typical phenomenon in the region of Central Europe, characterized by a complex, delicate, and constantly changing intersection of political, ethnic, national, linguistic, religious, cultural borders, and contexts, producing various competing collective identities. This article outlines this process in a multi-ethnic and multi-religious region. It shows how the concept of national identity was influenced by various loyalties, pragmatic political decisions, and ideological concepts. The idea of Slovak national identity was defined mainly in confrontation with Czech and Hungarian visions and concepts. It was shaped in the process of mutual correlation with other collective identities and also by its impact on the wide segments of population in the process of ‘national emancipation’.